Experimental tests of truncated diffusion in fault damage zones. Issue 11 (12th November 2016) - Suzuki, Anna; Hashida, Toshiyuki; Li, Kewen; Horne, Roland N.
Abstract: Fault zones affect the flow paths of fluids in groundwater aquifers and geological reservoirs. Fault‐related fracture damage decreases to background levels with increasing distance from the fault core according to a power law. This study investigated mass transport in such a fault‐related structure using nonlocal models. A column flow experiment is conducted to create a permeability distribution that varies with distance from a main conduit. The experimental tracer response curve is preasymptotic and implies subdiffusive transport, which is slower than the normal Fickian diffusion. If the surrounding area is a finite domain, an upper truncated behavior in tracer response (i.e., exponential decline at late times) is observed. The tempered anomalous diffusion (TAD) model captures the transition from subdiffusive to Fickian transport, which is characterized by a smooth transition from power‐law to an exponential decline in the late‐time breakthrough curves. Key Points: Fracture damage at fault zones decays to background levels with distance according to a power law Experimental results in the finite domain generate an upper truncated behavior in tracer response The tempered anomalous diffusion (TAD) model can capture the transition from subdiffusive to Fickian transport of tracer